Party Poppers and Balloons: Fun and Games or Lives and Limbs? Doi: 10.36351/pjo.v36i1.975 - Shaheen, Fiza; Naqaish, Rehan; Awan, Muhammad Amer (Pakistan Journal of Ophthalmology, 2020)
Abstract We report two cases of ocular trauma caused by recently popular party poppers and LED balloons, commonly used in parties nowadays. One case depicted a closed globe injury as a result of a party popper spray over the eye. The pressure of the spray resulted in a blunt trauma causing full thickness macular hole which was later treated with Pars Plana Vitrectomy (PPV) surgery. The second case is an example of an open globe injury caused by the bursting of LED balloon over the eye of a young child resulting in corneal perforation, traumatic cataract, vitreous hemorrhage with an intraocular foreign body (IOFB). It was successfully treated with corneal suturing, lens extraction, PPV surgery and removal of IOFB followed by a secondary lens implantation. Both of the sustained injuries were completely avoidable hence emphasizing the requirement of eye safety awareness programs and diligence in the use of these gadgets in everyday lives.